Variability in inflectional forms of attributive-appositive composite lexical units in Polish. (March 2021) - Cetnarowska, Bożena
Abstract : This paper examines inflectional markers (signalling number, case and gender) of selected types of NN complexes in Polish, which can be regarded as attributive-appositive (ATAP) lexical units in the cross-linguistic classification of compounds proposed by Scalise & Bisetto (2009) . Polish compounds proper show externalization of inflection and take inflectional markers on their right-hand constituents only. In contrast, Polish juxtapositions are expected to display double inflectional marking (on both their components). However, data from the National Corpus of Polish demonstrate that ATAP juxtapositions containing the lexeme widmo 'ghost, phantom' as their right-hand component exhibit variability in their inflectional paradigms. The right-hand (i.e. the modifier) constituent of such juxtapositions either shows number and case agreement with the head noun, or it appears in the default (nom.sg ) form. Potential reasons for the instability of inflectional paradigms of such NN juxtapositions are considered.